Post-Pandemic Banking Resilience: Examining the Influence of Risk Profile, Earnings, and Capital on Stock Prices in Indonesia - Natalia, Patricia Sharon; Pernamasari, Rieke (Universitas Sultan Ageng Tirtayasa, 2025)
This study aims to analyze the influence of risk profile, profitability, and capital on stock prices in conventional banking companies listed on the Indonesia Stock Exchange (IDX). The independent variables used in this study include Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), Return on Assets (ROA), and Capital Adequacy Ratio (CAR), which reflect fundamental banking performance dimensions in determining market valuation.The study population consists of all conventional banks listed on the IDX during the 2022–2023 period, totaling 43 companies. The sample was selected using the purposive sampling method, resulting in 86 observations. Data analysis was conducted using descriptive tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing, with data processing performed using SPSS 26. The results indicate that, simultaneously, NPL, LDR, ROA, and CAR have a significant affect on stock prices, suggesting that these factors collectively play a crucial role in determining banking stock valuation. However, on a partial basis, only the ROA variable has a significant affect on stock prices, while NPL, LDR, and CAR do not exhibit a significant influence. These findings confirm that profitability, as represented by ROA, is the dominant factor in determining banking stock prices, whereas credit risk, liquidity, and capital adequacy do not individually affect stock prices significantly.